The Molecular Pathology of Odontogenic Tumors: Expanding the Spectrum of MAPK Pathway Driven Tumors - Guimarães, Letícia Martins; Coura, Bruna Pizziolo; Gomez, Ricardo Santiago; Gomes, Carolina Cavalieri (Frontiers in Oral Health, 2021)
Odontogenic tumors comprise a heterogeneous group of lesions that arise from the odontogenic apparatus and their remnants. Although the etiopathogenesis of most odontogenic tumors remains unclear, recently there has been some advance in the understanding of specific odontogenic tumors’ genetic basis. The MAPK/ERK pathway is intimately involved in the regulation of important cellular functions, and it is commonly deregulated in several human neoplasms. Molecular analysis performed by different techniques, including direct sequencing, next-generation sequencing as well as allele-specific qPCR, have uncovered mutations in genes related to the oncogenic signaling pathway MAPK/ERK in odontogenic tumors. Genetic mutations in this pathway genes have been reported in epithelial and mixed odontogenic tumors, in addition to odontogenic carcinomas and sarcomas. Notably, BRAF and KRAS pathogenic mutations have been reported in a high proportion of ameloblastomas and adenomatoid odontogenic tumors, respectively. In line with reported for other neoplasms that harbor a malignant counterpart, the frequency of BRAF p.V600E mutation is higher in ameloblastoma (64% in conventional, 81% in unicystic, and 63% in peripheral) than in ameloblastic carcinoma (35%). This study aims to review MAPK/ERK genetic mutations in benign and malignant odontogenic tumors. Additionally, such genetic alterations are discussed in the context of tumorigenesis, clinical behavior, classification, and future perspectives regarding therapeutic approaches.